Morphological, biochemical and molecular identification of the wild strain of Agrobacterium tumefaciens from crown gall infected mango tree - Mst. Lailatul Ferdous; Md. Najmul Hossain; Md. Osman Ali; Md. Shahidul Islam; Sabina Yasmin (Fundamental and Applied Agriculture, 2021)
BACKGROUND: Mango (Mangifera indica) is a very important fruit and it is attractive for its delicious aroma and flavor. Mango is susceptible to various types of pathogens that result in decline of its fruit production. An important pathogen, Agrobacterium tumefaciens attacks on mango plant and it causes crown gall disease. The present study was conducted to isolate and identify Agrobacterium tumefaciens from crown gall samples. METHODOLOGY: These samples were collected from BAU campus, Mymensingh. The bacterium was isolated and characterized by morphological, microscopic, biochemical, and confirmed by molecular test. KEY FINDINGS: The morphological, microscopic and biochemical tests initially revealed that all the bacterial isolates are gram negative. Pathogenicity test: a carrot disc bioassay showed tumors in the plant because T-DNA of the bacteria was transferred and integrated into each of carrot disc. Antibiotic sensitivity tests revealed that the resistance to antibiotic. Moreover, DNA was isolated from infected tissue and after gel electrophoresis of PCR product, DNA band with expected 184bp was found and therefore, it was finally confirmed that the isolates were Agrobacterium tumefaciens. CONCLUSION: This bacterium has ability to alter hosts genome, thus, is considered in plant biotechnology as one of the natures best genetic engineer, antitumor studies and researches other purposes. [Fundam Appl Agric 2021; 6(1.000): 43-49]